ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI SPLTV DITINJAU DARI MULTIPLE INTELLIGENCES PESERTA DIDIK KELAS X MIPA SMAS DIPONEGORO TUMPANG TAHUN PELAJARAN 2020/2021 - Nurul Mahfiroh (De Fermat : Jurnal Pendidikan Matematika, 2021)
This study aims to describe the ability of mathematical problem solving in the SPLTV material in terms of multiple intelligence of class X MIPA students at SMAS Diponegoro Tumpang in the 2020/2021 academic year. The research method used in this research is descriptive qualitative. The subjects of this study were 6 students who were selected through the results of the multiple intelligence questionnaire, including 2 students who had mathematical logical intelligence, 2 students with intrapersonal intelligence, and 2 students with interpersonal intelligence. The techniques of data collection used in this study were multiple intelligence tests, mathematical problem solving tests, and interviews. Dominant research subjects with logical-mathematical intelligence have better skills in solving mathematical problems than other types of intelligence in solving mathematical problems and can practice concepts the concept algorithmically and present concepts in various mathematical representations. It is very important for educators to know and understand what kind of intelligences that students have. It is intended as a material for making lesson plans. So that the learning process can run smoothly, effectively, efficiently, and not only result-oriented.